2007
DOI: 10.1016/j.juro.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Vesicoureteral Reflux, Urinary Tract Infection and Renal Damage in Children

Abstract: There was a significant relationship between grade II vesicoureteral reflux and higher and permanent renal damage in boys and girls. However, while the association between renal damage and vesicoureteral reflux was evident in boys, the role of urinary tract infection and renal inflammation seemed to be equally or more important in girls. These findings support the concept that renal damage is associated with vesicoureteral reflux and is often congenital in boys, while in girls it is more related to urinary tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
1
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 21 publications
4
74
1
11
Order By: Relevance
“…(table IV) This figure is similar to the study done by Bhatnagar et al 11 in India where they found 62% children with UTI had VUR ( majority in grade V) but higher than the studies done by the other workers of different countries. 17,18,20,24 Zaki et al found the incidence of reflux 22%. 31 This difference may be due to that our country and India have more or less similar geographical, cultural and socioeconomic background and both the studies were done in tertiary level hospital and the patients reach there late due to parental ignorance, poverty and late referral by the primary and secondary care givers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(table IV) This figure is similar to the study done by Bhatnagar et al 11 in India where they found 62% children with UTI had VUR ( majority in grade V) but higher than the studies done by the other workers of different countries. 17,18,20,24 Zaki et al found the incidence of reflux 22%. 31 This difference may be due to that our country and India have more or less similar geographical, cultural and socioeconomic background and both the studies were done in tertiary level hospital and the patients reach there late due to parental ignorance, poverty and late referral by the primary and secondary care givers.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20]21,22, The lowest prevalence is in black Americans 6%-12%. [2][3][4] Venhola et al conducted a large study on children with UTI in Finland recently and had shown that 36% of children with proven UTI , 28% with possible UTI and 36% with improbable UTI had associated VUR.…”
Section: Discussionmentioning
confidence: 99%
“…UTIs were tabulated by severity, where possible, and the grade of VUR was recorded based on the initial cystogram. Sonographically determined renal length was tabulated for all ultrasounds obtained The relationship between urinary tract infections (UTIs), renal scarring, and vesicoureteral reflux (VUR) has been investigated in multiple studies over numerous decades [1][2][3][4][5]. Even though renal failure secondary to the interaction of VUR and UTI is decidedly rare, the relationship is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent renal damage has been reported to occur more often in patients with VUR of radiologic grade II or higher (16). Because scintigraphic pelvic reflux is equivalent to radiologic grade II or higher reflux, we included patients with scintigraphic pelvic reflux in this study.…”
Section: Discussionmentioning
confidence: 99%